Influence of quantum dot concentration on the opto-electronic properties of colloidal quantum-dots LEDs - Nguyen, Huu Tuan; Das, Raja; Duong, Anh Tuan; Lee, Soonil (Optical Materials, 2020)
We fabricated and studied the operation characteristics of light emitting devices (LEDs) based on green CdSe/ZnS quantum dots (QDs). A series of devices with different concentrations of QDs in toluene showed typical electroluminescence (EL) peaks that are consistent with green photoluminescence of colloidal QDs emitting layer (EML), but their bandwidth were varied due to the parasitic emission originating from the adjacent organic layers. Upon the increase of the QD concentration, the contribution of the color contamination to emission light from QD-LED (QLED) devices was decreased resulting in the narrowing of EL spectra. On the other hand, the maximum efficiency of QLEDs increased in the lower QD concentration range, while decreased in the higher range. The optimum luminous efficiency of 1.22 cd/A and the external quantum efficiency of 0.43% at standard video brightness (200 cd/m2) was observed from the device with a QD concentration of 6 mg/ml which can be attributed to the enhanced charge recombination in QD EML.
Keywords: CdSe/ZnS quantum dots; Charge recombinations; Colloidal quantum dots; External quantum efficiency; Green photoluminescence; Light emitting devices; Operation characteristic; Optoelectronic properties; Electroluminescence; QD concentration; QD EML; QLEDs